Kepuasan pekerjaan dalam kalangan jururawat dl Hospital Universiti Sains Malaysia (HUSM) - Emi, Hussien (Universiti Sains Malaysia, 2008)
The goal of this study is to identify the level of job satisfaction among nurses at Hospital Universiti Sains Malaysia (HUSM). Three medical and three surgical wards in HUSM are selected. The wards that have been choose are 7Utara, 7Selatan, 6Selatan, 21ntan, 3Utara, and 2Selatan. The subjects that have answered the questionnaires are 64 nurses from all chosen wards. The subjects are selected using random sampling. Data are obtained using selfreport questionnaires. Job Satisfaction Survey Questionnaire is used for assessing level of job satisfaction among nurses in HUSM. The data are processed with SPSS version 12.0. The data are analyzed using descriptive statistic and independent t-test for answering the research question. The result shows that HUSM nurses has moderate level of job satisfaction with min score 116.69 (SO= 9.67}. The nurse has high job satisfaction for coworker {min= 3.63} and the nature of work (min= 3. 78}. Level of job satisfaction are low for contingent rewards (min= 2.94) and operation condition {min= 2.77}. Overall, the differences of job satisfaction level among nurses at HUSM that working in different ward are not significantly different {t= 0.50). The differences of job satisfaction among nurses at HUSM that has different education level are not significantly different (t= 0.26). As a conclusion, job satisfaction level of nurses at HUSM is moderate. There is no difference of job satisfaction level among nurses at HUSM that working at different ward. There also no difference of job satisfaction level among nurses that has different level of education.